Epidemiologic estimate of the proportion of fatalities related to occupational factors in Finland - Nurminen, Markku; Karjalainen, Antti (Scandinavian Journal of Work, Environment & Health, 2001)
' ' OBJECTIVES ': 'This study attempts to estimate the proportion of annual deaths related to occupational factors in Finland and considers related methodological issues and associated uncertainties. ' ' METHODS ': 'Statistics on causes of death, numbers of subjects exposed, and risk ratios obtained from the epidemiologic literature were used to estimate the population attributable fraction and disease burden for causes of death from work-related diseases. Gender-, age- and disease-specific numbers of deaths were provided by Statistics Finland for 1996. Information on the size of the population, broken down by gender, age, occupation, and industry, was acquired from population censuses. A Finnish job-exposure matrix supplied data on the prevalence of exposure for specific agents and the level of exposure among exposed workers. ' ' RESULTS ': 'The attributable fraction of work-related mortality in the relevant age categories was estimated to be 7% (10% for men and 2% for women), and for all ages the fraction was 4%. For the main cause-of-death categories, the attributable fractions became 12% for circulatory system diseases, 8% for malignant neoplasms, 4% for respiratory system diseases, 4% for mental disorders, 3% for nervous system diseases, and 3% for accidents and violence. The following estimates were obtained for specific important diseases: 24% for lung cancer, 17% for ischemic heart disease, 12% for chronic obstructive pulmonary disease, and 11% for stroke. Based on these fractions, the total number of work-related deaths that occurred in Finland in 1996 was calculated to be on the order of 1800 (employed work force of 2.1 million); 86% involved men. ' ' CONCLUSIONS ': 'High-quality epidemiologic studies and national survey data are essential for obtaining reliable estimates of the proportion of deaths attributable to occupational factors. The magnitude of work-related mortality is an insufficiently recognized contributor to total mortality in Finland, especially from circulatory diseases and other diseases caused by exposure to agents other than asbestos.
Keywords: attributable fraction; burden of disease; epidemiologic estimate; epidemiologic method; fatality; Finland; health statistics; occupational exposure; occupational factor